2006
DOI: 10.1196/annals.1374.003
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsiosis in Europe

Abstract: In Europe, rickettsioses are long-known infectious diseases. Until recently, it was thought that Mediterranean spotted fever due to Rickettsia conorii was the only tick-borne rickettsiosis in Europe. In the last decade new Rickettsia spp. have been implicated in human pathology (R. slovaca, R. sibirica mongolotimonae, R. helvetica). Furthermore, cases of infection due to flea-borne rickettsioses (R. typhi, R. felis) have been described. Finally, although no outbreak of epidemic typhus has been reported yet in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 58 publications
1
27
1
2
Order By: Relevance
“…I n recent years, Europe has experienced an increase in the incidence of certain zoonoses, particularly those transmitted by arthropod vectors, such as rickettsiosis (Blanco and Oteo 2006). The number of methods available for detecting and identifying rickettsia has increased and allowed the detection of new rickettsial pathogens as well as already-known types in new locations.…”
Section: Introductionmentioning
confidence: 99%
“…I n recent years, Europe has experienced an increase in the incidence of certain zoonoses, particularly those transmitted by arthropod vectors, such as rickettsiosis (Blanco and Oteo 2006). The number of methods available for detecting and identifying rickettsia has increased and allowed the detection of new rickettsial pathogens as well as already-known types in new locations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these host species may potentially be exposed to R. helvetica. R. helvetica is a suspected pathogen in humans, and the symptoms described for infections in humans include fever, headache, arthralgia, and myalgia (1,3,7,21,34). The agent also has been implicated in two cases of fatal perimyocarditis (20,22).…”
mentioning
confidence: 99%
“…uals have a local black eschar at the site of tick inoculation [19] (figure 6). A study conducted in Crete reported sheep and goats as Reactions to bed bug bites vary among individuals.…”
Section: Clinical Featuresmentioning
confidence: 99%